Research progress of qiweibaizhu powder in treating digestive system diseases - Shi-Qi Liu; Ji Li (World Journal of Traditional Chinese Medicine, 2021)
Diarrhea is a common clinical problem that can lead to health complications, including death. It is the second-most common cause of death in children. The World Health Organization introduced a program to encourage the development and use of traditional herbal medicines in the treatment of diarrhea. Qiweibaizhu Powder (QWBZP) is a well-known pediatric prescription in China that is commonly used to treat digestive system diseases, such as diarrhea, which is also a type of syndrome in traditional Chinese medicine. Many studies have examined the clinical effects and mechanisms of QWBZP, and innovative and improved formulations have been developed. Recent studies on the effects of QWBZP on diarrhea caused by human rotavirus, antibiotic-associated diarrhea, and mesenteric lymphadenitis in experimental models and clinical trials with diarrhea patients have been reviewed. We conducted a literature search of several databases, including PubMed, China National Knowledge Infrastructure, Chongqing VIP Information Co., Ltd., and Wanfang. A short background of the QWBZP is also provided. The collective findings highlight the curative effects of QWBZP on diarrhea caused by viral infection, antibiotic use, and mesenteric lymphadenitis. Furthermore, QWBZP can regulate the balance of the gastrointestinal microbiota and protect and repair the intestinal mucosal barrier. This review will provide a reference for further studies on QWBZP.